(3GdQjGVjGJ hJWHjbGJgG aj GdYdhe GdEOGQjI hGdELJeGYjI (B/s - (3CfJhf, ghGQOs; (3chdef, HQGfGQOs ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 2002)
(3GdefWb GdQjGVj(B-(3fXQjI GdaFGJ(B-(3GdHQeLI GdNWjI(B((3GdMd GdgfOSj(B)-(3GdLHQ GdNWj,GdHQeLI GdNWjI(B((3GdWQjbI GdLHQjI(B)(3WQb GdYO(B-(3GdJHGOd hGdJhGab(B-(3GdEMJeGdGJ(B-(3fXQjI GdeHGQjGJs
Keywords: (3GdEOGQIs; (3GdQjGVjGJ GdJWHjbjIs; (3GdYdhe GdELJeGYjIs